Damping Factor Of Precast Concrete With Wet Connection - Hery Riyanto (University of Bandar Lampung (UBL), 2013)
This research aims at determining the behaviour of structural elements of precast reinforced concrete beams which are connected with wet and dry connections. Specimen used was 30 Mpa reinforced concrete beams with 6 pieces of 8 mm diameter main reinforcement which are placed on two rollers at the joint pedestal of each end and has a rectangular cross section of prismatic 10x18 cm2. Wet connection is a connection that uses a polymer concrete material of 40 MPa with a grafting method using prepacked method. The result of the research is expected to contribute to the development of precast concrete in building construction in Indonesia. In the elastic condition, the beam monolith has the largest natural frequency of the value, but a wet connection beam has a low natural frequency value. The difference of this natural frequency value is also equal to the condition of crack and ultimate.